Industry 4.0 and smart manufacturing convergence: profiling guidelines for a fourth revolution - Henry Avila, John; de JesÃºs Gil-Herrera, Richard (International Journal of Engineering and Technology, 2020)
Nowadays, all companies are subject to new global trends related to smart manufacturing, connectivity, information technologies applications, big cloud-based data analysis, Cyber-Physical Systems, among others. These factors generate changes in the supply chain of manufacturing and service companies. According to literature reviewing, the applicable central model of the new trends, which allows these companies to face these changes, has been in continues movement. To understand the behavior of these trends, a documentary review related to Industry 4.0 and Smart Manufacturing as trends that outline the fourth industrial revolution, is facing through this work. As result of this review, the authors to develop holistically a semantic representation of the main terms of descriptive figures and graphs, some components and terminology related to Industry 4.0 and Smart Manufacturing. As main conclusion, this reached integrated view, aimed to establish a semantic guideline of the fourth industrial revolution that may be also applicable to the enterprise no matter its size.Â Â